Prevalence and Characterization of Fluoroquinolone Resistant Salmonella Isolated From an Integrated Broiler Chicken Supply Chain - Cui, Mingquan; Zhang, Peng; Li, Jiyun; Sun, Chengtao; Song, Li; Zhang, Chunping; Zhao, Qi; Wu, Congming (Frontiers in Microbiology, 2019)
The objectives of this study were to investigate the prevalence and fluoroquinolone resistant Salmonella isolated from an integrated broiler chicken supply chain and their molecular characterization. In total, 73 Salmonella isolates were recovered from a broiler chicken supply chain in Shanghai. Salmonella isolates were tested for susceptibility to 11 antimicrobial agents using the broth dilution method and were characterized using pulsed-field gel electrophoresis (PFGE). Then, the Salmonella isolates were examined for mutations in quinolone resistance-determining region (QRDR) of gyrA, gyrB, parC, and parE, and were screened for plasmid-mediated quinolone resistance (PMQR) genes. Lastly, we sequenced the plasmids carrying qnrS1 in six Salmonella isolates from three sources (two isolated per source). Among 73 Salmonella isolates, 45 isolates were identified as S. Indiana, 24 were S. Schwarzengrund, 2 were S. Enteritidis, and 2 were S. Stanleyville. In addition, high rates of resistance were detected for nalidixic acid (41.1%) and ciprofloxacin (37.0%), while resistance to other test agents was diverse (2.0-100%). S. Indiana and S. Schwarzengrund isolates from different sources exhibited the same PFGE pattern, suggesting that the Salmonella isolates possessed high potential to spread along the broiler chicken supply chain. gyrA and parC exhibited frequent missense mutations. Moreover, qnrS1 was the most prevalent PMQR gene in the 73 Salmonella isolates, and it was found about a new hybrid plasmid. This study concludes a high prevalence of fluoroquinolone resistant Salmonella in chicken supply chain, threatening the treatment of Salmonella foodborne diseases. In particular, the emergence of a new hybrid plasmid carrying qnrS1 indicates that the recombination of plasmid carrying resistance gene might be a potential risk factor for the prevention and control strategies of drug resistance.